Peran Budaya Organisasi: E-Leadership, Kinerja Karyawan, dan Manajemen Perubahan dalam Anggota Tim Hybrid - Maria Ona Gracias; Rina Anindita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to analyze the Role of Organizational Culture in Electronic Leadership, Change Management, Employee Performance in hybrid teams with a minimum working period of 1-2 years as permanent employees in application development service companies. The population of this study was conducted to 215 respondents who work in IT department application development service companies. This research was conducted by distributing online questionnaires. The data processing method uses SEM PLS. In this study, it can be concluded that companies that have good Electronic Leaders can influence and strengthen the Organizational Culture and can also form a new Change Management, this can affect Employee Performance. When there is a tendency to change, electronic leaders must be able to overcome it by implementing an Organizational Culture related to the importance of being ready to accept change as the main key for hybrid team members in facing work-related challenges in a changing work environment. Electronics leaders must also be able to provide change management techniques by making pre-planning transitions to perfecting practical technologies in hybrid teams such as technology automation provided by the company for project trackers. Researchers found that electronic leadership influences change management and organizational culture but has no effect on employee performance. Then organizational culture has an influence on employee performance and change management.